Enhanced Negative Magnetoresistance with High Sensitivity of Polyaniline Interfaced with Nanotitania. Issue 8 (1st January 2016) - Guo, Jiang; Guan, Litao; Wei, Huige; Khan, Mojammel A; Zhang, Xin; Li, Bingbing; Wang, Qiang; Weeks, Brandon L.; Young, David P.; Shen, Tongde; Wei, Suying; Guo, Zhanhu
Abstract : Unique negative giant magnetoresistance (GMR) of up to −43% at room temperature was observed in the 10 wt% titania/polyaniline (TiO2 /PANI) nanocomposites prepared by simple oxidation polymerization. And the negative MR value was further evaluated using forward interference model. Other properties were tested and comparatively reported. The resistivity of TiO2 /PANI nanocomposites decreased with increasing temperature, indicating a semiconductor behavior. The Mott variable range hopping (VRH) approach indicated that TiO2 /PANI nanocomposites are disordered systems in the 3-dimensional VRH regime. The scanning electron microscope (SEM), high resolution transmission electron microscopy (HRTEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) were also used to study morphology, chemical and crystal structure of the nanocomposites. The thermogravimetric analysis (TGA) was used to study the thermal stability of the TiO2 /PANI nanocomposites.